Senandung dan Ayunan: Cukupkah untuk menghentikan tangisan bayi? - Casman; Sri Melfa Damanik; Risna Yuningsih (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Infants aged 0-12 months sleep 10-18 hours per day. Deep sleep in babies has been shown to affect brain development, so it is critical to ensure the baby is sound asleep. Parents must be able to provide a safe environment for their baby and know how to calm them when they cry. Indonesian culture and values have a strong influence on the care of babies after birth. Swinging is a method that mothers have used since primitive times to muffle their baby's crying.Objective: The purpose of this study is to describe the efforts of mothers in Indonesia who swing while humming to calm crying babies.Methods: This study is a simple narrative review in which articles were found using three databases: neliti.com, garuda.kemdikbud.go.id, and Google scholar. Swinging and ngayun are some of the keywords used.Results: According to the search results, 8 out of 187 articles explain that swinging (baayun, bapukung, and ngayun) and humming (dindang, lulabi, or lullabies) are effective in calming children when they cry and can induce sleep in babies.Conclusion: In babies, the process of swinging, which is usually followed by humming, can reduce both the duration and frequency of crying